Ultrasonography in diagnosis of necrotizing enterocolitis - Frederico Celestino Miranda; Yoshino Tamaki Sameshima; Alice D’ Agostini Deutsch; Arno Norberto Warth; Miguel Jose Francisco Neto; Marcelo Buarque de Gusmão Funari (Einstein (São Paulo), 2009)
Necrotizing enterocolitis is one of the most frequent gastrointestinal emergencies in neonates, and it is generally detected clinically and radiographically. Early diagnosis is fundamental in order to limit morbidity and mortality. At the beginning of the disease, classical findings, such as abdominal distension and intestinal pneumatosis may not be detectable by conventional radiographs. In these cases, ultrasonography may help in early diagnosis. It is presented a case of necrotizing enterocolitis in a preterm newborn whose diagnosis was only possible via ultrasonography.